Method for preparing furfuryl alcohol through furfural gas phase hydrogenation by using phosphorus-modified Cu / MgO-P core-shell catalyst

By using phosphorus-modified Cu/MgO-P core-shell catalysts, the problem of insufficient catalytic performance and stability of existing chromium-free catalysts in the preparation of furfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurfurf

CN119897103APending Publication Date: 2025-04-29SHENYANG INSTITUTE OF CHEMICAL TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839576.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing chromium-free catalysts have insufficient catalytic performance and stability in the preparation of furfurfural alcohol during the gas-phase hydrogenation of furfural, resulting in low furfural conversion and furfurfural alcohol selection, and high by-product selectivity, affecting economic benefits.

Method used

The phosphorus-modified Cu/MgO-P core-shell catalyst is used. This catalyst uses non-precious metal Cu as an active component and MgO as a support to improve the acidic site of the catalyst through phosphorus modification, enhance the dispersion of Cu and its interaction with the support, reduce carbon deposits, and improve the activity and stability of the catalyst.

Benefits of technology

The furfural conversion rate is greater than 98%, the furfural alcohol selectivity is higher than 96%, the by-product selectivity is low, and the catalyst has no obvious inactivation after 800 hours of operation, which has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing furfuryl alcohol through furfural gas phase hydrogenation by using a phosphorus-modified Cu / MgO-P core-shell catalyst, and relates to a reaction method for preparing furfuryl alcohol by using a catalyst. The catalyst adopts non-noble metal Cu as a catalyst active component and magnesium oxide as a carrier, and phosphorus is introduced into the catalyst for modification. The content of Cu in the catalyst reaches 20%-60%, the content of carrier MgO is about 80%-40%, and the dosage of NH4H2PO4 used for phosphorus modification is calculated according to 0.1%-2% of the total mass of the catalyst. The furfuryl alcohol selectivity of the catalyst is high, so that better economic benefits are obtained, the catalyst has high activity and stability, the furfural conversion rate is larger than 98% when the catalyst is used for furfural, and the furfuryl alcohol selectivity is higher than 96%. Good industrial application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing furfuryl alcohol by hydrogenation of a catalyst, and in particular to a method for preparing furfuryl alcohol by hydrogenation of furfural by a phosphorus-modified Cu / MgO-P core-shell catalyst in gas phase. Background Art

[0002] Furfuryl alcohol (FOL) is mainly used to produce furan resins with various properties, such as furfuryl alcohol urea-formaldehyde resin and phenolic resin. These resins have the advantages of acid and alkali resistance and other chemical corrosion, and are widely used in the fields of mechanical industry, precision casting core binder, etc., which helps to improve casting quality, realize the mechanization of casting process and reduce costs. In addition, furfuryl alcohol can also be used as anti-corrosion resin, pharmaceutical raw material, preparation of fruit acid, solvent, plasticizer, etc. The plasticizer made from furfuryl alcohol has better cold resistance than esters of butanol and octanol. Furfuryl alcohol is also a good solvent and rocket fuel for furan resin, varnish, pigment, and can be used in synthetic fiber, rubber, pesticide and foundry industry. Furfural (FUR) is known as an important biomass platform compound due to its unique chemical structure, wide application field, renewable biomass source and feasibility of industrial production. Its use in the production of furfuryl alcohol is of great significance for sustainable development.

[0003] There are various types of existing catalysts for the gas phase hydrogenation of furfural to furfuryl alcohol. Copper chromite catalysts are usually used in gas phase hydrogenation processes. However, the presence of chromium substances that are harmful to the environment and human health and their moderate activity have prompted the development of chromium-free catalysts. So far, many chromium-free catalysts have been reported, including Pd, Pt, Co, Ni and Fe, which have been applied to the hydrogenation of furfural.

[0004] Among them, copper-based catalysts are considered to be the most promising catalysts for industrial applications, and copper-magnesium (Cu-Mg) system catalysts are widely used in copper-based catalysts and show great potential in the hydrogenation of furfural to produce furfuryl alcohol. By optimizing the preparation method, additives and carriers of the copper-magnesium system, the catalytic performance of the catalyst can be improved to a certain extent. BMNagaraja et al. reported (BM Catalysis Communications, 2003, 4 (6), 287-293.) that furan, tetrahydrofuran, tetrahydrofurfuryl alcohol, methylfuran and other products may be generated during the hydrogenation of furfural. Wu et al. (Jing Wu, Catalysis Communications, 2005, 6 (9), 633–637.) reported that Cu-Ca / SiO prepared by sol-gel method 2The catalyst showed higher copper dispersion and higher activity than the catalyst prepared by impregnation method. Li et al. (Feng Li, Canadian Journal of Chemical Engineering, 2016, 94(7), 1368–1374.) found that in Cu / SiO 2 Add appropriate amount of TiO to the catalyst 2 , improving the dispersibility of Cu particles and inhibiting the growth of Cu particles, thereby increasing the yield of furfuryl alcohol. These studies show that the preparation method and the addition of additives have a significant effect on the dispersion of copper, thereby affecting the hydrogenation performance of furfural. Summary of the invention

[0005] The present invention aims to provide a method for preparing furfuryl alcohol by gas-phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst. The catalyst of the method adopts non-precious metal Cu as a catalyst active component, has a high selectivity for furfuryl alcohol, and thus obtains better economic benefits. The catalyst has high activity and stability, a furfural conversion rate of greater than 98%, and a furfuryl alcohol selectivity of greater than 96%, and has good industrial application prospects.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing furfuryl alcohol by gas-phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst, the method comprising the following steps:

[0008] (1) Weigh Cu salt and Mg salt, add deionized water to prepare a metal salt solution, and stir at room temperature to completely dissolve them;

[0009] (2) Then, the salt solution and the alkaline solution are added to a beaker containing distilled water in parallel, stirring while adding, and the pH is first controlled at 7. After the salt solution is added, the alkaline solution is continued to be added to control the pH at 9 until the alkaline solution is completely added;

[0010] (3) Then, the mixture was stirred and aged for 3 h at room temperature, and then allowed to stand and aged for 1 h. The obtained precipitate was washed with deionized water several times and dried.

[0011] (4) Grind the product obtained from the first drying into a uniform and fine powder, and then impregnate the corresponding amount of NH 4 H 2 PO 4 aqueous solution, and drying it again; calcining the dried material to obtain a Cu / MgO-P catalyst;

[0012] (5) The catalyst is used for the gas phase hydrogenation of furfural.

[0013] The method for preparing furfuryl alcohol by gas-phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst, wherein the soluble Cu salt and Mg salt are both nitrates.

[0014] In the method for preparing furfuryl alcohol by gas-phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst, the concentration of the metal salt solution is 0.1-1.5 mol / L.

[0015] In the method for preparing furfuryl alcohol by hydrogenating furfural in gas phase using a phosphorus-modified Cu / MgO-P core-shell catalyst, the alkaline solution is a mixed solution of sodium carbonate and sodium hydroxide, or a mixed solution of potassium carbonate and potassium hydroxide, and the concentrations thereof are both 0.1-1.5 mol / L.

[0016] The method for preparing furfuryl alcohol by gas phase hydrogenation of furfural with a phosphorus-modified Cu / MgO-P core-shell catalyst, wherein the NH 4 H 2 PO 4 The solution is constant volume, and the catalyst after the first drying is taken. Each gram of catalyst in this state absorbs 1.5 ml of solution to determine the NH 4 H 2 PO 4 Solution volume.

[0017] The phosphorus-modified Cu / MgO-P core-shell catalyst is used to prepare furfuryl alcohol by hydrogenating furfural in gas phase, wherein the mass percentage of CuO is 20%-60%, the mass percentage of MgO is 80%-40%, and the mass percentage of NH 4 H 2 PO 4 The mass percentage accounts for 0.1%-2.0% of the Cu / MgO-P catalyst.

[0018] The method for preparing furfuryl alcohol by hydrogenating furfural in gas phase using a phosphorus-modified Cu / MgO-P core-shell catalyst comprises the following steps: the washing method is vacuum filtration; the drying method is drying in air at a drying temperature of 80-150°C; the drying time is 10-15h; the calcination method is air calcination at a calcination temperature of 300-600°C and a calcination time of 3-6h.

[0019] The method for preparing furfuryl alcohol by using a phosphorus-modified Cu / MgO-P core-shell catalyst for gas-phase hydrogenation of furfural is described. When the catalyst is used in the gas-phase hydrogenation reaction process of furfural, H 2 / N 2 Mixed gas reduction, after the reduction is completed, control the temperature to the reaction temperature, adjust N 2 The flow rate is 0, and the furfural feed flow rate and H 2 The feed flow rate is H 2 / FUR ratio, and then the gas phase catalytic hydrogenation reaction begins.

[0020] The method for preparing furfuryl alcohol by gas phase hydrogenation of furfural with a phosphorus-modified Cu / MgO-P core-shell catalyst, wherein the H 2 / N 2 The mixed gas is 20%-80% H 2 / N 2 Mixed gas, reduction temperature is 200-300℃, reduction time is 3-6h.

[0021] The method for preparing furfuryl alcohol by hydrogenating furfural in gas phase using a phosphorus-modified Cu / MgO-P core-shell catalyst, wherein the H 2 / FUR is 5-15, the reaction temperature is 120-160°C; the reaction pressure is normal pressure.

[0022] The salient features of the present invention are:

[0023] (1) Using non-precious metal Cu as the active component and MgO as the carrier, the catalyst has good stability and high selectivity for furfuryl alcohol.

[0024] (2) During the preparation process, by utilizing the precipitation conditions of Cu salt and Mg salt and improving the co-precipitation preparation method, Cu-Mg formed an obvious progressive core-shell structure, which enhanced the dispersion of Cu and its interaction with the carrier MgO, and effectively alleviated the agglomeration of Cu during the reaction.

[0025] (3) The introduction of phosphorus increases the acidic sites on the catalyst surface, which plays a good regulatory role on the acidic and alkaline sites on the catalyst surface and can effectively reduce carbon deposition during the use of the catalyst.

[0026] (4) The catalyst has high activity and stability, with a furfural conversion rate greater than 98% and a furfuryl alcohol selectivity greater than 96%. The main byproducts in the product are 2-methylfuran and tetrahydrofurfuryl alcohol, with a selectivity of less than 3%, and other products are rare. There is no obvious deactivation of the catalyst after running for 800 hours. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with specific embodiments:

[0028] According to the mass ratio of different components of the catalyst, a certain amount of Cu salt and Mg salt and a corresponding amount of deionized water are first weighed to mix them evenly, and then a certain amount of Na 2 CO 3Mix the NaOH and the corresponding amount of deionized water evenly, then add the two to 100 ml of deionized water in parallel, stirring thoroughly while adding, and keep the pH at about 7 during the parallel addition process. After the salt solution is completely added, the pH is controlled at about 9 during the addition of the alkaline solution. After the addition is completed, seal the bottle mouth, age at room temperature for 4 hours, dry overnight after the aging, grind the product obtained from the first drying into a uniform and fine powder, and then soak the corresponding amount of NH 4 H 2 PO 4 The aqueous solution is dried again. After drying, the catalyst is calcined at 400℃ for 4h to obtain the catalyst. Before use, it needs to be tableted, sieved, and then heated in H 2 / N 2 The reduction was carried out at 250°C for 4 hours at an air flow ratio of 20%-80%.

[0029] Example 1: 6g of copper nitrate trihydrate and 51g of magnesium nitrate hexahydrate were weighed and dissolved in 450ml of deionized water to prepare solution A. Then 12g of sodium carbonate and 15g of sodium hydroxide were weighed and dissolved in 580ml of deionized water to prepare solution B. Solution A and solution B were first kept at pH ≈ 7 and added dropwise to precipitate. Salt solution A was first added dropwise completely, and then the alkaline solution B was added dropwise to maintain pH ≈ 9. After the addition was completed, it was stirred and aged at room temperature for 3h, and then aged for 1h. After the end, it was washed with deionized water for 3-4 times. After the washing was completed, the product was dried for the first time. Then 0.10g of NH 4 H 2 PO 4 Dissolve in deionized water to form 15 ml of solution C, take 10 g of the product after the first drying and evenly add solution C on it to impregnate it. After aging for 24 hours, dry it again. After drying, grind the obtained product into uniform and fine powder, and then roast it at 400°C for 4 hours to obtain the catalyst.

[0030] Example 2: 12g of copper nitrate trihydrate and 38g of magnesium nitrate hexahydrate were weighed and dissolved in 400ml of deionized water to prepare solution A. Then 10g of sodium carbonate and 13g of sodium hydroxide were weighed and dissolved in 520ml of deionized water to prepare solution B. Solution A and solution B were first kept at pH ≈ 7 and added dropwise to precipitate. Salt solution A was added dropwise first, and then the alkaline solution B was added dropwise at a controlled flow rate to maintain pH ≈ 9. After the addition was completed, the solution was stirred and aged at room temperature for 3h, and then aged for 1h. After the addition was completed, the solution was washed with deionized water for 3-4 times. After the washing was completed, the product was dried for the first time. Then 0.11g of NH 4 H 2 PO 4Dissolve in deionized water to form 15 ml of solution C, take 10 g of the product after the first drying and evenly add solution C on it to impregnate it. After aging for 24 hours, dry it again. After drying, grind the obtained product into uniform and fine powder, and then roast it at 400°C for 4 hours to obtain the catalyst.

[0031] Example 3: 18g of copper nitrate trihydrate and 25g of magnesium nitrate hexahydrate were weighed and dissolved in 350ml of deionized water to prepare solution A. Then 9g of sodium carbonate and 11g of sodium hydroxide were weighed and dissolved in 450ml of deionized water to prepare solution B. Solution A and solution B were first kept at pH ≈ 7 and added dropwise to precipitate. Salt solution A was added dropwise first, and then the alkaline solution B was added dropwise at a controlled flow rate to maintain pH ≈ 9. After the addition was completed, the solution was stirred and aged at room temperature for 3h, and then aged for 1h. After the addition was completed, the solution was washed with deionized water for 3-4 times. After the washing was completed, the product was dried for the first time. Then 0.13g of NH 4 H 2 PO 4 Dissolve in deionized water to form 15 ml of solution C, take 10 g of the product after the first drying and evenly add solution C on it to impregnate it. After aging for 24 hours, dry it again. After drying, grind the obtained product into uniform and fine powder, and then roast it at 400°C for 4 hours to obtain the catalyst.

[0032] Example 4: 12g of copper nitrate trihydrate and 38g of magnesium nitrate hexahydrate were weighed and dissolved in 400ml of deionized water to prepare solution A, and 10g of sodium carbonate and 13g of sodium hydroxide were weighed and dissolved in 520ml of deionized water to prepare solution B. Solution A and solution B were first kept at pH ≈ 7 and added dropwise to precipitate. Salt solution A was first added dropwise, and then the alkaline solution B was added dropwise at a controlled flow rate to maintain pH ≈ 9. After the addition was completed, the solution was stirred and aged at room temperature for 3h, and then aged for 1h. After the addition was completed, the solution was washed with deionized water for 3-4 times. After the washing was completed, the product was dried for the first time. Then 0.03g of NH 4 H 2 PO 4 Dissolve in deionized water to form 15 ml of solution C, take 10 g of the product after the first drying and evenly add solution C on it to impregnate it. After aging for 24 hours, dry it again. After drying, grind the obtained product into uniform and fine powder, and then roast it at 400°C for 4 hours to obtain the catalyst.

[0033] Example 5: 12g of copper nitrate trihydrate and 38g of magnesium nitrate hexahydrate were weighed and dissolved in 400ml of deionized water to prepare solution A. Then 10g of sodium carbonate and 13g of sodium hydroxide were weighed and dissolved in 520ml of deionized water to prepare solution B. Solution A and solution B were first kept at pH ≈ 7 and added dropwise to precipitate. Salt solution A was added dropwise first, and then the alkaline solution B was added dropwise at a controlled flow rate to maintain pH ≈ 9. After the addition was completed, the solution was stirred and aged at room temperature for 3h, and then aged for 1h. After the addition was completed, the solution was washed with deionized water for 3-4 times. After the washing was completed, the product was dried for the first time. Then 0.06g of NH 4 H 2 PO 4 Dissolve in deionized water to form 15 ml of solution C, take 10 g of the product after the first drying and evenly add solution C on it to impregnate it. After aging for 24 hours, dry it again. After drying, grind the obtained product into uniform and fine powder, and then roast it at 400°C for 4 hours to obtain the catalyst.

[0034] Catalyst performance test

[0035] 1.0 g of the prepared catalyst particles were loaded into a reactor and heated under N 2 :H 2 =1:1 mixed gas at 250℃ for 4h. After the temperature of the reactor drops to the reaction temperature, turn off the N 2 And H 2 The flow rate was adjusted to 41 mL / min, and the raw material furfural was transported to the evaporator through an infusion pump and mixed with H 2 They are fed into a reactor together for reaction, and the obtained products are analyzed by gas chromatography.

[0036] When the reaction pressure is normal pressure, the reaction temperature is 160°C, and the liquid hourly space velocity is 1.04h -1 and H 2 Under the condition of / FUR ratio of 10, the catalyst was fed for 6 hours and the performance evaluation results are listed in Table 1.

[0037] Table 1 Catalyst performance evaluation results

[0038] Examples Furfural conversion rate (100%) Furfuryl alcohol selectivity (100%) 1 99.1 99.2 2 99.5 98.9 3 99.9 98.7 4 99.9 98.7 5 99.9 98.5 .

Claims

1. A method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst, characterized in that: The method comprises the following steps: (1) Weigh Cu salt and Mg salt, add deionized water to prepare a metal salt solution, and stir at room temperature to completely dissolve them; (2) Then, the salt solution and the alkaline solution are added to a beaker containing distilled water in parallel, stirring while adding, and the pH is first controlled at 7. After the salt solution is added, the alkaline solution is continued to be added to control the pH at 9 until the alkaline solution is completely added; (3) Then, the mixture was stirred and aged for 3 h at room temperature, and then allowed to stand and aged for 1 h. The obtained precipitate was washed with deionized water several times and dried. (4) Grinding the product obtained by the first drying into a uniform and fine powder, then impregnating a corresponding amount of NH4H2PO4 aqueous solution, and drying again; calcining the dried material to finally obtain a Cu / MgO-P catalyst; (5) The catalyst is used for the gas phase hydrogenation of furfural.

2. A method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: The soluble Cu salt and Mg salt are both nitrates.

3. A method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: The concentration of the metal salt solution is 0.1-1.5 mol / L.

4. A method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: The alkaline solution is a mixed solution of sodium carbonate and sodium hydroxide, or a mixed solution of potassium carbonate and potassium hydroxide, and the concentrations thereof are both 0.1-1.5 mol / L.

5. A method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: The NH4H2PO4 solution is constant volume, and the catalyst after the first drying is taken, and the volume of the NH4H2PO4 solution is determined by the fact that each gram of the catalyst in this state absorbs 1.5 ml of the solution.

6. The method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: The mass percentage of CuO is 20%-60%, the mass percentage of MgO is 80%-40%, and the mass percentage of NH4H2PO4 accounts for 0.1%-2.0% of the Cu / MgO-P catalyst.

7. The method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: The washing method is vacuum filtration; the drying method is drying in air, the drying temperature is 80-150°C; the drying time is 10-15h; the roasting method is air calcination, the roasting temperature is 300-600°C, and the roasting time is 3-6h.

8. The method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: When the catalyst is applied to the furfural gas phase hydrogenation reaction process, it is reduced with H2 / N2 mixed gas. After the reduction is completed, the temperature is controlled to the reaction temperature, the N2 flow rate is adjusted to 0, the furfural feed flow rate and the H2 feed flow rate are adjusted to obtain the H2 / FUR ratio, and then the gas phase catalytic hydrogenation reaction is started.

9. The method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: The H2 / N2 mixed gas is 20%-80% H2 / N2 mixed gas, the reduction temperature is 200-300°C, and the reduction time is 3-6h.

10. The method for preparing furfuryl alcohol by gas phase hydrogenation of furfural using a phosphorus-modified Cu / MgO-P core-shell catalyst according to claim 1, characterized in that: The H2 / FUR is 5-15, the reaction temperature is 120-160°C, and the reaction pressure is normal pressure.